A questionnaire-based study to assess the knowledge, attitude and behaviour about leprosy among paramedical staff in a tertiary care hospital in Chennai - Manoharan, D.; Kulkarni, Ojas Dipak; C., Geo Danny; Manoharan, K. (International Journal of Research in Medical Sciences, 2021)
Background: The paramedical staff has an important part in the management of leprosy patients. They have a role in counselling, wound management, performing investigations etc. This study aimed at assessing the knowledge, attitude and behaviour of paramedical workers in a tertiary care hospital in Chennai. Methods: This cross-sectional study comprised of 100 paramedical workers of which 41 were males and 59 were females. Following classes of workers were included: nursing staff, auxiliary nursing midwives, ASHA workers, laboratory technicians, pharmacists and allied medical workers. Of these, the nursing staff comprised of the highest proportion (44%). The paramedical workers were given a questionnaire consisting of their demographic profile and further 32 questions to assess knowledge, attitude and behaviour towards leprosy. The data hence obtained over a period of 1 month was later systematically analysed. Results: The knowledge of paramedical workers was considered sufficient in the nursing staff, ANM and ASHA workers. It was consistently found that those workers who had some experience in the field of leprosy (39%) showed good level of knowledge, while others had a scope for improvement. The paramedical workers’ attitudes and behaviour were deemed to be overall appropriate, while there is a clear need to improve outreach initiatives in order to properly train them. Conclusions: The training of paramedical workers in leprosy should be prioritised. They are the initial point of contact for patients. There should be a greater emphasis on raising awareness and providing accurate information about the disease.